International Human Rights Law and Women's Access to Abortion. - Gaudio, Amelia; Welch, Ryan M (International Studies Quarterly, 2025)
Can international law protect abortion rights? Drawing from past work on domestic mechanisms that give international law teeth, we argue that a strong civil society composed of women's groups and groups concerned with women's rights leads the government to comply with its international human rights commitments to women, specifically their right to abortion. Unlike that past work, though, we draw attention to the ways in which civil society can leverage the depth of their government's international legal commitment. Highly legalized commitments—those characterized by higher obligation, precision, and delegation—should help groups mobilize and give them access to international legal forums that can credibly threaten the government. Based on this argument, we expect countries that have ratified the Convention on the Elimination of Discrimination against Women's Optional Protocol, a highly legalized treaty, to protect women's rights to abortion when women's civil society participation is high. Estimating several statistical models to test our expectations, the results lend credence to the argument. Highly legalized commitments allow civil society actors to hold governments accountable to those commitments leading to more liberalized abortion rights protections.